Expression and significance of m6A-RNA-methylation in oral cancer and precancerous lesion - Qin, Zhiming; Bai, Jiaying; He, Huiying; Li, Binbin (Frontiers in Oncology, 2023)
Background: Oral potentially malignant disorders (OPMDs) and oral squamous cell carcinoma (OSCC) are a series of related pathologic and molecular events involving simple epithelial hyperplasia, mild to severe dysplasia and canceration. N6-methyladenosine RNA methylation, as the most common modification of both coding mRNA and non-coding ncRNA in eukaryotes, participates in the regulation of the occurrence and development of various malignant tumors in human. However, its role in oral epithelial dysplasia (OED) and OSCC remain unclear. Materials and methods: In this study, multiple public databases were used for bioinformatics analysis of 23 common m6A methylation regulators in head and neck squamous cell carcinoma (HNSCC). Protein expressions of IGF2BP2 and IGF2BP3 were verified accordingly in clinical cohort samples of OED and OSCC. Results: Patients with high expression of FTO、HNRNPC、HNRNPA2B1、LRPPRC、IGF2BP1、IGF2BP2、IGF2BP3 had a poor prognosis. IGF2BP2 had a relatively high mutation rate in HNSCC, and its expression was significantly positively correlated with tumor purity, and significantly negatively correlated with the infiltration level of B cells and CD8+T cells. The expression of IGF2BP3 was significantly positively correlated with tumor purity and CD4+T cells. Immunohistochemistrically, the expression of IGF2BP2 and IGF2BP3 in oral simple epithelial hyperplasia, OED and OSCC increased gradually. Both were strongly expressed in OSCC. Conclusion: IGF2BP2 and IGF2BP3 were the potential biological prognostic indicators of OED and OSCC.